2011
DOI: 10.1080/01608061.2011.619388
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Rewards and Work Stress

Abstract: Even though reward systems play a central role in the management of organizations, their impact on stress and the well-being of workers is not well understood. We review the literature linking performance-based reward systems to various indicators of employee stress and well-being. Well-controlled experiments in field settings suggest that certain types of performance-based reward systems, such as piece rate pay, cause increases in psychological and physiological stress. Such findings are mirrored in nonexperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…23 Similar results are obtained when comparing the baseline with our original stochastic treatment (see Figure B2 and Table B10 in Appendix B). The negative effect of ability on stress is in line with the empirical evidence suggesting that low performers experience more stress from performance-contingent rewards compared to fixed wages (Williams and Livingstone, 1994;Ganster et al, 2011). In the next section, we study the interaction effect between individual characteristics and the entropy of rewards on work persistence.…”
Section: Entropy and Stresssupporting
confidence: 71%
See 1 more Smart Citation
“…23 Similar results are obtained when comparing the baseline with our original stochastic treatment (see Figure B2 and Table B10 in Appendix B). The negative effect of ability on stress is in line with the empirical evidence suggesting that low performers experience more stress from performance-contingent rewards compared to fixed wages (Williams and Livingstone, 1994;Ganster et al, 2011). In the next section, we study the interaction effect between individual characteristics and the entropy of rewards on work persistence.…”
Section: Entropy and Stresssupporting
confidence: 71%
“…For example, there is ample evidence suggesting that performance-contingent pay systems are associated with higher levels of stress of the employees compared with fixed wages (Levi, 1972;Timio and Gentili, 1976;Timio, Gentili and Pede, 1979;Schleifer and Amick, 1989;Schleifer and Okobaga, 1990;Shirom, Westman and Melamed, 1999). In a review of this literature, Ganster et al, (2011) argue that this effect may be mediated by uncertainty and lack of job control, so performance-contingent rewards are especially stressful when the uncertainty about the relationship between effort and rewards is high. De Berker et al, (2016) have recently shown that the perceived uncertainty regarding the occurrence of an aversive stimulus (i.e., electric shock) was closely related to both self-reported and physiological measures of stress.…”
Section: Uncertainty and Stressmentioning
confidence: 99%
“…Whether the pressure to publish and indeed to generate research income is seen as a stressor or a challenge depends in large part on the extent to which a person feels in control of the outcomes (Ganster, Kiersch, Marsh, & Bowen, 2011). Academics may have some control over the number of papers they submit, however, most academics have far less control over the outcomes of publication, or research grant submissions or even what counts as a publication.…”
Section: The Potential Effects Of Ranking On Disciplinary Researchmentioning
confidence: 97%
“…For instance, in a recent UK academic well-being survey, more than half of the 14,677 respondents indicated high or very high levels of stress, and almost a third reported they often or always experienced unacceptable levels of stress (Kinman, 2014). Workplace stress is a major contributor to serious health problems (Ganster et al, 2011) and attrition. Indeed, a 2009-10 survey of 1,414 academics from eight institutions in Victoria, Australia, found that less than 30% of respondents would stay at their current institution if they were offered a decent job elsewhere (Fredman & Doughney, 2011).…”
Section: The Potential Effects Of Ranking On Disciplinary Researchmentioning
confidence: 99%
“…Even though performance based wages are fairly common in many countries, few studies have examined whether performance based wages are associated with any health consequences [ 1 ]. The few extant studies have, however, linked performance based wages with signs of poorer health.…”
Section: Introductionmentioning
confidence: 99%